Decreased monocyte activation with daily acyclovir use in HIV-1/HSV-2 coinfected women. (22nd April 2015) - Redd, Andrew D; Newell, Kevin; Patel, Eshan U; Nalugoda, Fred; Ssebbowa, Paschal; Kalibbala, Sarah; Frank, Melanie A; Tobian, Aaron A R; Gray, Ronald H; Quinn, Thomas C; Serwadda, David; Reynolds, Steven J
Abstract : Objectives: Several clinical trials have demonstrated that daily treatment of HIV-infected individuals with the antiherpes drug acyclovir slightly decreases HIV-1 viral load and slows disease progression. This study examines if this slowing in clinical progression is a direct cause of the decrease in viral load or an indirect effect of lower immune activation due to lower levels of herpetic reactivation. Methods: Women who participated in a randomised clinical trial of daily acyclovir use (n=301) were monitored every 6 months for changes in immune activation. Soluble CD14 (sCD14), a marker for monocyte activation, and C-reactive protein (CRP), a marker for general immune activation, were measured by ELISA. Results: Initial levels of sCD14 and CRP were not predictive of HIV disease progression when controlling for initial CD4+ cell count and HIV viral load. sCD14 levels, but not CRP, decreased in the acyclovir treatment arm at a significantly faster rate than the placebo group, which was independent of changes in HIV viral load and CD4+ cell count in a multivariant mixed-effects model (p=0.039). However, the magnitude of this decrease was relatively small with a total estimated decrease of sCD14 of 15% of initial levels. Conclusions: These data suggest that decreased monocyte activation may play a minor role in the ability of daily acyclovir use to slow HIV disease progression. Clinical trial registration number: NCT00405821